Phenomenology and the Concept of Consciousness - Cherono, Abigale (International Journal of Philosophy, 2024)
Purpose: The general objective of the study was to explore phenomenology and the concept of consciousness. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to phenomenology and the concept of consciousness. Preliminary empirical review revealed a complex relationship between subjective experience and cognitive and neural mechanisms. It demonstrated that phenomenology, focusing on first-person perspectives and intentionality, offers a robust framework for understanding consciousness as an active, embodied engagement with the world. The integration of phenomenological insights with cognitive science and neuroscience provided a comprehensive view, correlating subjective reports with neural activity. This approach proved valuable in clinical settings, enhancing mental health interventions by focusing on individual experiences. The study highlighted the promise of ongoing interdisciplinary research to advance both scientific and philosophical understandings of consciousness. Unique Contribution to Theory, Practice and Policy: The Theory of Intentionality, Embodies Cognition Theory and Global Workspace Theory may be used to anchor future studies on phenomenology and the concept of consciousness. The study recommended further development of theoretical frameworks integrating phenomenology with cognitive neuroscience, emphasizing the need for interdisciplinary research collaborations. It suggested incorporating phenomenological approaches into mental health practices to enhance patient-centered care and advocated for training healthcare professionals in these methods. The study also advised policymakers to integrate phenomenological findings into mental health policies and prioritize funding for programs that recognize subjective experiences. Lastly, it highlighted the need for future research to explore long-term effects, cultural factors, and new neuroimaging techniques to advance the understanding of consciousness.